2018
DOI: 10.1200/jgo.2016.008664
|View full text |Cite
|
Sign up to set email alerts
|

Underuse of Radiation Therapy After Breast Conservation Surgery in Puerto Rico: A Puerto Rico Central Cancer Registry–Health Insurance Linkage Database Study

Abstract: PurposeTo identify rates of postoperative radiation therapy (RT) after breast conservation surgery (BCS) in women with stage I or II invasive breast cancer treated in Puerto Rico and to examine the sociodemographic and health services characteristics associated with variations in receipt of RT.MethodsThe Puerto Rico Central Cancer Registry–Health Insurance Linkage Database was used to identify patients diagnosed with invasive breast cancer between 2008 and 2012 in Puerto Rico. Claims codes identified the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
4
0
2
Order By: Relevance
“…30 , 31 This could potentially lead to more advanced stage at diagnosis and/or delayed access to preventive and treatment services as research has shown that patients with public health coverage in PR experience longer waiting times to schedule an appointment, to see a specialist, and to receive cancer treatment. 10 , 30 , 32 35 More studies are needed to understand how type of health coverage affects survival in PR.…”
Section: Discussionmentioning
confidence: 99%
“…30 , 31 This could potentially lead to more advanced stage at diagnosis and/or delayed access to preventive and treatment services as research has shown that patients with public health coverage in PR experience longer waiting times to schedule an appointment, to see a specialist, and to receive cancer treatment. 10 , 30 , 32 35 More studies are needed to understand how type of health coverage affects survival in PR.…”
Section: Discussionmentioning
confidence: 99%
“…17 También se asemeja a estudios realizados en Estados Unidos y Puerto Rico donde el 66.2% y 64.0% de mujeres recibieron radioterapia adyuvante post cirugía conservadora en un periodo de 10 años, con tasa anual de 60.9%-70.1%. 14,20 Sin embargo, la totalidad de las pacientes deben recibir radioterapia posterior a la cirugía conservadora, debido a la reducción del 70.0% de las recurrencias locales y 50.0% la tasa anual de falla en los primeros 10 años. 21,22 Hasta la fecha no se ha identificado un subgrupo de pacientes en el que la radioterapia pueda ser seguramente omitida.…”
Section: Discussionunclassified
“…Se registró datos sociodemográficos, estadio clínico pre-y post-operatorio, tratamiento y sobrevida. Resultados: De 49 pacientes, 59.2% (29) >50 años, 71.4% (35) procedencia urbana, 61.2% (30) estadio IIA, las modalidades terapéuticas fueron radioterapia 73.5% (36), hormonoterapia 69.4% (34), quimioterapia 40.8% (20). La combinación más frecuente fue radioterapia/hormonoterapia 46.9% (23); 26.5% (13) recibió monoterapia.…”
unclassified
See 1 more Smart Citation
“…Also, the lack of training, protocols, and palliative care teams and specialists [ 9 ] may exacerbate the gap between the need for palliative care services and availability of these services in the island. This is of great concern because lack of appropriate and timely use of oncologic health services may contribute to the observed differences in cancer-related health outcomes and survival [ 7 , 10 ]. Therefore, understanding the barriers to standards of care is essential for addressing the disparities in the burden associated with symptom distress experienced by the NSCLC population, which can ultimately result in a low quality of life for these patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%